2018
DOI: 10.1521/pdps.2018.46.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Data about the Validation of a Self-Report for the Assessment of Interpersonal Guilt: The Interpersonal Guilt Rating Scales–15s (IGRS-15s)

Abstract: The aim of this article is to present validation data about a self-report rating scale for the assessment of interpersonal guilt according to Control-Mastery Theory (CMT; Silbershatz, 2005; Weiss, 1993; Weiss, Sampson, & The Mount Zion Psychotherapy Research Group, 1986), the Interpersonal Guilt Rating Scale-15s (IGRS-15s). In order to perform the validation of this tool in an Italian sample we have collected a sample of 645 nonclinical subjects. They had to complete the IGRS-15s, the Scale for the Measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 55 publications
5
23
0
Order By: Relevance
“…Overall, our data support the constructs of the different kinds of guilt as conceptualized in CMT and assessed with the IGRS-15s: Survivor guilt and Omnipotence guilt-which in a previous study (Gazzillo et al, 2018) were found to be connected to the basic affective systems of care, attachment, and fear-were connected to the empathy felt for other people's suffering, contributed to feelings of shame and low self-esteem, negatively affected well-being and mental health, and were stronger in people who felt that during their development their caregiver had more problems than they did, needed their help, or appeared burdened by them or pained by their separation and differentiation. Self-hate, for its part-which the same previous study showed to be connected to attachment and fear motivational systems but not to the care system-was not correlated with empathy, negatively affected self-esteem, well-being, and mental health, stirred up feelings of shame, and negatively influenced therapeutic alliance, as did Survivor guilt.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Overall, our data support the constructs of the different kinds of guilt as conceptualized in CMT and assessed with the IGRS-15s: Survivor guilt and Omnipotence guilt-which in a previous study (Gazzillo et al, 2018) were found to be connected to the basic affective systems of care, attachment, and fear-were connected to the empathy felt for other people's suffering, contributed to feelings of shame and low self-esteem, negatively affected well-being and mental health, and were stronger in people who felt that during their development their caregiver had more problems than they did, needed their help, or appeared burdened by them or pained by their separation and differentiation. Self-hate, for its part-which the same previous study showed to be connected to attachment and fear motivational systems but not to the care system-was not correlated with empathy, negatively affected self-esteem, well-being, and mental health, stirred up feelings of shame, and negatively influenced therapeutic alliance, as did Survivor guilt.…”
Section: Discussionsupporting
confidence: 87%
“…A three-factor analysis solution model (Survivor guilt; Omnipotence guilt; Self-hate), based on previous research with this tool (IGRS-15s; Gazzillo et al, 2018), was proposed. Confirmatory factor analysis (CFA) and network analysis of 448 cases were conducted.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations